2010
DOI: 10.5012/bkcs.2010.31.03.653
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of (-)-Clavosolide A and B

Abstract: Enantioselective total synthesis of (-)-clavosolide A and B was reported in full including the synthesis of proposed structure of (-)-clavosoldie A (1), revised structure of (-)-clavosoldie A (5), and revised structure of (-)-clavosoldie B (6). The relative and absolute stereochemistries of the natural products were confirmed unambiguously by comparing the optical rotation values and 1 H and 13 C NMR spectra of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 74 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Our synthesis commenced from acetonide 3 (>97% ee), 5 a known enantiopure compound prepared from d -mannitol ( Scheme 2 ). 6 After sequential acidic deprotection of the isopropylidene group of 3 and oxidative cleavage with periodic acid, 7 the aldehyde was methylated with MeMgBr and the resulting secondary alcohol was oxidized with 2-iodoxybenzoic acid (IBX) to afford cyclopropyl ketone 4. 8 C 2 -Homologation of cyclopropyl ketone 4 by the Horner–Wadsworth–Emmons reaction afforded α,β-unsaturated esters 5 and 6 in 95% yield ( E : Z = 9 : 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our synthesis commenced from acetonide 3 (>97% ee), 5 a known enantiopure compound prepared from d -mannitol ( Scheme 2 ). 6 After sequential acidic deprotection of the isopropylidene group of 3 and oxidative cleavage with periodic acid, 7 the aldehyde was methylated with MeMgBr and the resulting secondary alcohol was oxidized with 2-iodoxybenzoic acid (IBX) to afford cyclopropyl ketone 4. 8 C 2 -Homologation of cyclopropyl ketone 4 by the Horner–Wadsworth–Emmons reaction afforded α,β-unsaturated esters 5 and 6 in 95% yield ( E : Z = 9 : 1).…”
Section: Resultsmentioning
confidence: 99%
“…Despite these impressive results, progress in asymmetric intermolecular samarium Reformatsky reactions is still slow, in particular, enals were only rarely employed as electrophilic substrates. Such stereoselective cross-couplings would be interesting because the resulting β-hydroxy-γ-alkenyl-ketones (amides, esters or acids) are subunits of natural products such as eremofortin F, stellatolide H, stellettapeptins A and B, mohangic acids, ieodomycin C, or largazole (Figure ). Furthermore, they are valuable synthetic scaffolds for the synthesis of complex target molecules, as was exemplified in the total synthesis of pleuraspiroketals A, B, (−)-clavosolide A, B, bistramide K, solomonamide, azaspirene, dolatrienoic acid, and ferrulactone . The β-hydroxy-γ-alkenyl-ketone unit has been previously accessed via stereoselective aldol reactions using Evans oxazolidinones. …”
Section: Introductionmentioning
confidence: 99%
“…25 The β-hydroxy-γ-alkenyl-ketone unit has been previously accessed via stereoselective aldol reactions using Evans oxazolidinones. 26−29 Regarding chirality transfer, these studies revealed that the aldol addition of boron enolates strongly favored the syn-aldol products and the stereogenic centre at C-4 of the oxazolidinone directed the hydroxy group to the opposite face, 21,26,28 while the E-or Z-configuration of the enal had almost no influence on the stereochemical outcome of the C−C coupling (Scheme 1, routes a−c). 28 In contrast, the samarium Reformatsky reactions reported by Fukuzawa 5 and Burke 9 provided the β-hydroxyimides lacking an α-substituent with the hydroxy group and the stereodirecting isopropyl moiety of the Evans auxiliary positioned on the same side (Scheme 1, routes d and e).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Unique structural features of 1 have attracted considerable interest from the synthetic community. 2 Willis and co-workers reported the first total synthesis of the proposed structure ( 2 ) of the natural product, which led to the revision of the configuration of the trans -cyclopropanes. 2a Later, the total synthesis of 1 by Lee and co-workers confirmed the structural revision.…”
mentioning
confidence: 99%
“…Iodine-mediated dithiane-deprotection of 4 (88%) followed by NaBH 4 -reduction of the resulting ketone afforded secondary alcohol 12 in 90% yield (Scheme 4). Glycosylation of 12 with phenyl thioglycoside 13 2a in the presence of MeOTf gave the desired β -anomeric monomer 14 (65%, dr = 3.8:1). 8 The Simmons–Smith cyclopropanation of 14 provided cyclopropane 3 (71%) as a single diastereomer.…”
mentioning
confidence: 99%